Análisis del contenido de carotenoides florales de plantas que crecen en la provincia de Buenos Aires (Argentina) - Natalucci, Claudia Luisa (1982)
Flowers of nineteen wild and cultivated species growing in the Province of Buenos Aires have been investigated for their total carotenoid, carotene, mono- and dihidroxycarotenoid contents. Yellow and orange floral varieties of Tagetes erecta L. were also studied for comparative purposes. Carotenes are the main fraction in six species and xanthophylls in the others. Within the latter is Ranunculurs repens L., with a total carotenoid content even higher than the orange variety of T. erecta.